The Role of the Teacher in Instilling Tauhid-Based Education in Students in the Perspective of the Qur'an - Haerul Haerul; Iqra Iqra; Barakat Muhammad Ahmad Muhammad Hamad Al-Nil; Rania Mahmoud ELSakhawy (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
This paper aims to explore and describe the role of teachers in instilling tawhid-based education in students in the Qur'an. So that educators can provide positive injections about education, especially training and learning in tawhid, to students. This research uses library research, which collects data that refers to books, the Quran, scientific journals, and previous research that is considered relevant as a data source in the study. Tauhid education is education that leads to the knowledge of the oneness of Allah. Tauhid is a fundamental science that Muslims must own because Tauhid is the basis of belief and belief in Tauhid. In instilling Tauhid education, the critical role of an educator in the world of education, which will encourage students to learn about religious knowledge constantly, is needed to develop students' understanding. Teachers provide advice, lectures, and exercises in worshipping Allah, such as prayer, fasting, and other vertical relationships between humans and God. Of course, it must be supported by the persistence of the family who always provides education for their children because parents/family are the first madrasah for children. The cultivation of monotheistic education cannot be separated from the Al-Quran verses and the Prophet Muhammad's arguments as a source of law in Islam. Moreover, that should be the basic principle in providing religious education to students. The kinds of Tauhid that need to be instilled are the Tauhid of Uluhiyah, the Tauhid of Rububiyah, and the Tauhid of Asma' Wa Sifat.